Hannibal rising : a novel - Harris, Thomas (New York : Delacorte Press, 2006)
Chronicles serial killer Hannibal Lecter's childhood and early adulthood after being taken from a Soviet orphanage to live with his uncle and aunt in France. He becomes the youngest person ever to attend medical school in France.
Keywords: Spirits -- Fiction; Psychological fiction